PENGARUH PROBIOTIK BAGI KESEHATAN USUS (STUDI KASUS: PROBIOTIK TEH KOMBUCHA) - Selita Wiscana (SUAN PUBLISHER, 2025)
This study aims to investigate the effects of routine kombucha tea consumption on gut health, specifically focusing on the modulation of intestinal microbiota and the reduction of functional gastrointestinal symptoms. Using a quasi-experimental approach with a pre-test and post-test design, 30 adult respondents with mild digestive complaints were selected via purposive sampling. The participants were intervened with 200 ml of standardized kombucha tea (containing 10^7 to 10^8 CFU/ml of Lactic Acid Bacteria) daily for 21 days. Data were collected using the Gastrointestinal Symptom Rating Scale (GSRS) to measure digestive discomfort and the Bristol Stool Chart to evaluate bowel movement frequency and stool consistency. The results demonstrated a significant reduction in GSRS scores, particularly in dimensions of bloating and abdominal pain. Furthermore, 70% of respondents reported a transition toward ideal stool types (Type 3 and 4) on the Bristol Stool Chart, indicating an improvement in intestinal transit time and peristaltic activity. The symbiotic relationship between the live microorganisms in the SCOBY (Symbiotic Culture of Bacteria and Yeast) and the tea polyphenols proved effective in suppressing pathogenic bacteria and restoring gut homeostasis. This study concludes that kombucha tea serves as a potent non-dairy probiotic alternative that significantly enhances digestive function. These findings advocate for the integration of traditional fermented beverages into modern diets as a preventive strategy against functional gastrointestinal disorders